Periodontal Health Status and Level of Periodontal Treatment Needs in Stroke Patients at Hasan Sadikin Hospital Bandung - Rani Sukmawati; Kartika Indah Sari; Agus Susanto; Lisda Amalia (Journal of Indonesian Dental Association, 2020)
Introduction: A stroke is any form of brain disorder or central nervous system damage caused by altered blood flow to the brain that impairs motor and cognitive function. Impaired motor and cognitive function restrict oral hygiene, so these patients are vulnerable to dental health problems, such as periodontal disease. They often require help from family members to assist them with oral care. Objectives: The aim of this study was to describe the condition of periodontal tissue and the periodontal treatment needs of stroke patients. Method: This research is a descriptive study using a cross-sectional format. It was conducted at Hasan Sadikin Hospital Bandung with a sample of 30 stroke patients. An examination of periodontal status and periodontal treatment needs was performed using an index from the World Health Organization, the Community Periodontal Index of Treatment Needs (CPITN). Results: None of the patients had healthy periodontal tissue status (score 0), gingival bleeding during or after probing (score 1), or a periodontal pocket ≥ 6 mm (score 4). Nine patients (30%) had supragingival or subgingival calculus (score 2), and 21 patients (70%) had 4–5 mm periodontal pockets (score 3). Conclusion: Most stroke patients at Hasan Sadikin Hospital Bandung had a pocket depth of 4–5 mm, and their periodontal health status indicated a need for scaling, root planing, removal of plaque retentive factors, and oral hygiene instructions.